Changes in the levels of acute-phase protein and other serum protein fractions in Santa Inês ewes fed with a high-concentrate diet - Girardi, Annita Morais [UNESP]; Sabes, Amanda Festa [UNESP]; Fagliari, José Jurandir [UNESP]; Silva, Paulo César da [UNESP]; Oliveira, João Ademir de [UNESP]; Marques, Luiz Carlos [UNESP] (Elsevier, 2018)
The aim of this study was to evaluate the effects of subacute ruminal acidosis (SARA) on total serum protein (TP), plasma fibrinogen (Fb), and serum protein fractions in seven hay-adapted Santa Inês ewes fed with a high-concentrate diet for 133 days. Blood was extracted, before feeding, by external jugular venipuncture into tubes with ethylenediaminetetraacetic acid dipotassium anticoagulant, to evaluate the Fb concentration by heat precipitation, and into plain tubes, for TP analysis by the Biuret method and for sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). SDS-PAGE obtained the following proteins: immunoglobulin A (IgA) and G (IgG); ceruloplasmin (Cp); transferrin (Tf); albumin; α1-antitrypsin (α1AT); haptoglobin (Hp); α1-acid glycoprotein (α1AG); and 140, 101, 95, 46, 36, 34, 31, and 23 kDa molecular weight proteins (MWP). Associations among variables and time were evaluated using regression analysis. Fb concentrations did not change (P > 0.05); IgA, α1AT, and Hp levels increased, while Cp decreased throughout the period. Mean Tf levels increased, reaching the highest value on the 72nd day. The other protein levels oscillated during the study. A positive correlation, measured using Pearson's coefficient, was found between TP and IgG levels (r = 0.77; P < 0.0001). IgA, Hp, Tf, and α1AT showed greater potential for use in the diagnosis of SARA. The occurrence of proteins with unknown functions, but that have been highly influenced by the high-grain diet, increases the possibility of identifying inflammatory markers for SARA.
Keywords: Acute-phase proteins; Inflammation; Lipopolysaccharides; Serum globulins; Serum protein electrophoresis